Dna fragmentation in hela cells treated with Brucea javanica fruits extract - Noor Hidayu, Pathni (Pusat Pengajian Sains Perubatan Universiti Sains Malaysia, 2008)
Fruits of Brucea javanica (B. javanica) have been used as traditional medicine in China as it has been shown to have antimalarial, antiplasmodial, antitumor or anticancer and antiamoebic. In this study, methanol extracts of B. javanica fruit (BJF) were treated on human cervical cancer cell (HeLa). Antiproliferative activity of BJF methanol extracts on HeLa cells showed ICso value of 13.34 J.l.g/ml. After that, TUNEL assay (Terminal Deoxynucleotide Transferase dUTP Nick End Labeling) was done to detect the apoptosis rate of BJF methanol extract on HeLa cells. The apoptosis rate for 24 h, 48 h and 72 h were 13.8%, 17.8% and 22.9% respectively. The percentage of apoptosis rate was time dependent. These results proposed that BJF methanol extracts exhibits antiproliferative effect on HeLa cells by inducing apoptosis. Therefore, it may be a potential candidate for antiproliferative agent for the treatment of human cervical cancer cells.